Coupled numerical simulation and strategy optimization of land subsidence caused by groundwater extraction in Langfang City - Yongjie Xie; Ge Fu; Haipeng Guo; Jianfeng Qi; Kaijie Guo; Yunlong Wang; Shixiong Tian (PLoS ONE, 2026)
Numerical simulation is an effective method for studying land subsidence caused by groundwater extraction. In this paper, the land subsidence in Langfang City was analyzed by using a coupled fluid-solid three-dimensional numerical simulation. Firstly, four aquifer groups were divided into several aquifers and aquitards, and a finite element model was established. Previous studies often used the Mohr-Coulomb model or linear elastic models to describe the mechanical properties of aquitards, but these models are unable to capture yield characteristics under hydrostatic pressure, whereas the Cam-clay model can reflect this behavior. Based on groundwater level and monitoring data by layered settlement gauges from Danfeng Park, the model was validated. The results indicate that the Cam-clay model effectively simulates the deformation behavior of aquitards. Secondly, 15 different extraction scenarios were used to analyze the variations in pore water pressure in the aquifers, deformation of the aquitards, deformation of 4 aquifer groups, and land subsidence. The study showed that the deformation of aquitards within the pumping-affected zone is predominantly plastic, and it was found that the forms of plastic deformation include strain hardening, strain softening, and the critical state. Further analysis revealed that, under the same extraction volume, deep groundwater extraction had a greater impact on pore water pressure, plastic deformation of the aquitards, and land subsidence compared to shallow groundwater extraction. Finally, a comparative analysis of groundwater extraction scenarios was conducted, and a reasonable extraction scenario was proposed, providing a scientific basis for groundwater resource development and land subsidence control in Langfang City.